PERAN KHITOBAH DALAM MEMBENTUK MENTAL SANTRI DI PONDOK PESANTREN MISLAKHUL MUTA’ALIMIN WARUNGPRING, PEMALANG - Azizah, Deha Farihatul; Mukromin, Mukromin; Kamal, Faisal (FAKULTAS ILMU TARBIYAH DAN KEGURUAN UNIVERSITAS SAINS AL-QUR'AN, 2023)
Khitobah is the delivery of ideas and thoughts about Islam for approximately seven minutes. Each student delivered his khitobah in front of the congregation, hoping to build the children's confidence and spark bright ideas in the minds of the students. Therefore, in pesantren it is necessary to hold evangelistic activities to convey the thoughts of students in public and train the students' mentality. The formation of self-motivation is very important, not only requires self-motivated people to memorize yellow papers, but also requires self-motivated people to be able to develop in various fields, especially when self-motivated people have gone downhill.